Observation of anomalous side-scattering in laser wakefield accelerators. (31st October 2018) - Krushelnick, K.; Dangor, A. E.; Kaluza, M.; Mangles, S. P. D.; Murphy, C. D.; Najmudin, Z.; Thomas, A. G. R.
Abstract: High-intensity femtosecond laser–plasma interaction experiments were performed to investigate laser–plasma wakefield acceleration in the "bubble" regime. Using a 15 TW laser pulse, the emission of side-scattered radiation was spectrally and spatially resolved and was consequently used to diagnose the evolution of the laser pulse during the acceleration process. Side-scattered emission was observed immediately before wavebreaking at a frequency of ωL + 1.7ωp (where ωL is the laser frequency and ωp is the background plasma frequency). This emission may result from scattering of laser light by large amplitude plasma oscillations generated in the shell of the wakefield "bubble" and which occurs immediately prior to the wavebreaking/injection process. The observed variation of the frequency of scattered light with electron density agrees with theoretical estimates.